DEVELOPMENT OF SYLLABUS WRITING DESCRIPTION BASED ON PICTURE AND PICTURE MEDIA IN CLASS IV ELEMENTARY SCHOOL - Nurjani Nurjani (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
The problem of this research is inspired by the lack of students' ability in learning to write descriptions. Therefore the purpose of this research is to produce a syllabus for writing a description based on picture and picture media that is valid, practical, and effective. The model used in this study is the ADDIE (Analysis), (Design), (Develop), (Implement), and (Evaluate) models. The participant in this study were students and teachers of SDN 01 Simabur. The validity instrument is seen from the learning syllabus sheet validation. The practicality instrument can be seen from the observation sheet of the implementation of the lesson plan, as well as the teacher and student opinion questionnaire. Instruments of effectiveness can be seen from the observation of student activities and the results of student skills in writing. The type of data in this study is primary data. The results of the validity test by experts and practitioners are categorized as very valid namely 90% and 87%. The practicality of the syllabus is categorized as very practical, evidenced by observing the implementation of the RPP with a percentage of 89%, and supported by the teacher and student responses of 90% and 91%. Finally, the effectiveness felt by students in writing descriptions is considered very effective, which can improve students' ability to write descriptions. In short, the development of syllabus writing description based on picture and picture media in grade IV elementary school can be declared valid, practical, and effective